Glial promoter selectivity following AAV-delivery to the immature brain. - Georg von Jonquieres (Public Library of Science (PLoS), 2013)
Recombinant adeno-associated virus (AAV) vectors are versatile tools for gene transfer to the central nervous system (CNS) and proof-of-concept studies in adult rodents have shown that the use of cell type-specific promoters is sufficient to target AAV-mediated transgene expression to glia. However, neurological disorders caused by glial pathology usually have an early onset. Therefore, modelling and treatment of these conditions require expanding the concept of targeted glial transgene expression by promoter selectivity for gene delivery to the immature CNS. Here, we have investigated the AAV-mediated green fluorescent protein (GFP) expression driven by the myelin basic protein (MBP) or glial fibrillary acidic protein (GFAP) promoters in the developing mouse brain. Generally, the extent of transgene expression after infusion at immature stages was widespread and higher than in adults. The GFAP promoter-driven GFP expression was found to be highly specific for astrocytes following vector infusion to the brain of neonates and adults. In contrast, the selectivity of the MBP promoter for oligodendrocytes was poor following neonatal AAV delivery, but excellent after vector injection at postnatal day 10. To extend these findings obtained in naïve mice to a disease model, we performed P10 infusions of AAV-MBP-GFP in aspartoacylase (ASPA)-deficient mouse mutants presenting with early onset oligodendrocyte pathology. Spread of GFP expression and selectivity for oligodendrocytes in ASPA-mutants was comparable with our observations in normal animals. Our data suggest that direct AAV infusion to the developing postnatal brain, utilising cellular promoters, results in targeted and long-term transgene expression in glia. This approach will be relevant for disease modelling and gene therapy for the treatment of glial pathology.